PtrMYB120 functions as a positive regulator of both anthocyanin and lignin biosynthetic pathway in a hybrid poplar. (7th June 2021) - Kim, Min-Ha; Cho, Jin-Seong; Bae, Eun-Kyung; Choi, Young-Im; Eom, Seok Hyun; Lim, You Jin; Lee, Hyoshin; Park, Eung-Jun; Ko, Jae-Heung
Abstract: Both anthocyanins and lignins are essential secondary metabolites in plant growth and development. Their biosynthesis is metabolically interconnected and diverges in the central metabolite 4-coumaroyl CoA of the phenylpropanoid pathway. Considerable progress has been made in understanding transcriptional regulation of genes involved in lignin and anthocyanin synthesis pathways, but the concerted regulation of these pathways is not yet fully understood. Here, we functionally characterized PtrMYB120, a R2R3-MYB transcription factor from Populus trichocarpa . Overexpression of PtrMYB120 in a hybrid poplar (i.e., 35S::PtrMYB120) was associated with increased anthocyanin (i.e., cyanidin 3- O -glucoside) accumulation and upregulation of anthocyanin biosynthetic genes. However, transgenic poplars with dominant suppression of PtrMYB120 function achieved by fusing the ERF-associated amphiphilic repression motif to PtrMYB120 (i.e., 35S::PtrMYB120-SRDX) had a dramatic decrease in not only anthocyanin but also Klason lignin content with downregulation of both anthocyanin and lignin biosynthetic genes. Indeed, 35S::PtrMYB120-SRDX poplars had irregularly shaped xylem vessels with reduced S-lignin content in stems, which was proportionally related to the level of the introduced PtrMYB120-SRDX gene. Furthermore, protoplast-based transcriptional activation assay using the PtrMYB120-GR system suggested that PtrMYB120 directly regulates genes involved in both anthocyanin and lignin biosynthesis, including chalcone synthase and ferulate-5 hydroxylase . Interestingly, the saccharification efficiency of line #6 of 35S::PtrMYB120-SRDX poplars, which had slightly reduced lignin content with a normal growth phenotype, was dramatically enhanced (>45%) by NaOH treatment. Taken together, our results suggest that PtrMYB120 functions as a positive regulator of both anthocyanin and lignin biosynthetic pathways and can be targeted to enhance saccharification efficiency in woody perennials.